Growth of rhizopus oligosporus in sago effluent at different pH - Nur Aqlily Riana, binti Nasar (Universiti Malaysia Sarawak (UNIMAS), 2015)
The discharge of large amounts sago effluent into the river leads to severe water pollution. A study on the growth of R. oligosporus in the sago effluent at different pH was carried out. R. oligosporus was grown for the treatment of sago effluent with the production of high protein fungal biomass (HPFB) via submerged fermentation (SmF). The objectives of this study were to investigate the optimum pH for the growth of R. oligosporus in sago effluent and the effectiveness of SmF by R. oligosporus for water treatment. Sago effluent was adjusted to pH 4, 5, 6 and one replicate with no adjustment of pH. The optimum pH for R. oligosporus was notable at pH 4. The highest wet and dry biomass production of pH 4 were 98.67 g/L and 3.80 g/L respectively. There were three analysis that were successfully carried out which were phenol sulphuric test, nitrate and nitrite analysis. There was 98% reduction of carbohydrate concentration in sago effluent. Besides, the nitrate concentration was reduced from 0.266 to 0.257 g/L in pH 4. Concentration of nitrite was decreased from 0.040 to 0.029 g/L in pH 4. In addition to the production of HPFB, the decreasing of starch, nitrate and nitrite concentration would lead to a potential benefits to the environment.